The Meaning of the Word "Homeland" According to the Perspective Indonesian Nation - Endro Tri Susdarwono (Jurnal Masyarakat Maritim, 2025)
The term “homeland” holds a profound and multidimensional meaning in the context of the Indonesian nation, reflecting not only a geographical territory but also an emotional, cultural, and ideological bond uniting diverse ethnic groups within one national identity. This study explores the meaning of “homeland” (tanah air) from a sociocultural and philosophical perspective, emphasizing its significance in shaping national consciousness and patriotism among Indonesians. Using a qualitative descriptive approach, this research analyzes literary works, historical narratives, and cultural expressions that illustrate how the Indonesian people conceptualize their homeland as both physical land (tanah) and life-giving water (air). The findings reveal that the word “homeland” symbolizes the inseparable relationship between people and nature, portraying Indonesia as a living entity that nurtures and sustains its citizens. It embodies a sense of belonging, sacrifice, and shared destiny rooted in collective struggle against colonialism and the aspiration for independence. From a sociological viewpoint, “homeland” functions as a moral and emotional foundation that strengthens social solidarity and unity amidst diversity. It also serves as a source of identity and pride that motivates citizens to protect national sovereignty and preserve cultural heritage. The study concludes that, for the Indonesian nation, the word “homeland” transcends territorial boundaries—it represents a spiritual and symbolic space where history, identity, and national ideals converge. Strengthening this awareness is crucial to maintaining unity and resilience in an era of globalization and cultural transformation.